Impact of Cloud Computing on Data Security in E-Commerce Applications in Brazil - Rocha, Alves (International Journal of Computing and Engineering, 2024)
Purpose: The purpose of this article was to analyze impact of cloud computing on data security in e-commerce applications in Brazil. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Cloud computing has significantly impacted data security in e-commerce applications in Brazil by offering both advantages and challenges. While cloud services enhance scalability, flexibility, and cost-effectiveness, they also introduce concerns regarding data privacy, regulatory compliance, and vulnerability to cyberattacks. E-commerce businesses in Brazil face issues like data breaches and unauthorized access, which are exacerbated by insufficient local regulations and security standards. However, with proper encryption, multi-factor authentication, and adherence to global security frameworks, these risks can be mitigated. Unique Contribution to Theory, Practice and Policy: Technology acceptance model (TAM), diffusion of innovations (DOI) theory, resource-based view (RBV)may be used to anchor future studies on the impact of cloud computing on data security in e-commerce applications in Brazil. From a practical standpoint, e-commerce businesses leveraging cloud computing must adopt a multi-layered security approach to protect sensitive data. Policymakers should focus on creating comprehensive cloud security standards tailored to the needs of the e-commerce sector.